Effect of Combined Alkali (KF + CsF) Post‐Deposition Treatment on Cu(InGa)Se2 Solar Cells. Issue 10 (30th August 2018) - Kim, Shinho; Tampo, Hitoshi; Shibata, Hajime; Matsubara, Koji; Niki, Shigeru
Abstract : This study reveals combined alkali (KF + CsF) post‐deposition treatment (PDT) effects on a Cu(InGa)Se2 (CIGSe) cell. Three different alkali‐PDTs (KF, CsF, and combined KF + CsF) on CIGSe thin films have been performed. The CIGSe cell with KF‐PDT exhibits further reduction in the recombination at the CdS/buffer interface, whereas the CIGSe cell with CsF‐PDT exhibits further reduction in the recombination in bulk. In addition, the CIGSe cell with combined alkali‐PDT exhibits reduced recombination at both the CdS/CIGSe interface and in bulk compared to all other cells. By applying the combined alkali‐PDT, a highly efficient CIGSe device with 20.15% is achieved. Abstract : The CIGSe cell with combined alkali (KF + CsF) post‐treatment deposition (PDT) exhibits improved solar cell efficiency compared to those with single‐alkali‐PDT. This improvement can be owing to cooperative alkali incorporation effects; KF‐PDT leads to further reduction in the recombination at the CdS/buffer interface, whereas CsF‐PDT leads to further reduction in the recombination in bulk.